Evaluacion de hibridos trilineales de maiz (Zea mays L.) en 6 ambientes de Centroamerica y El Caribe, 1989 - Perez, C.=700 1 Soto, N.; Aguiluz, A.; Celado, R.; Jimenez, K.; Urbina, R.; Cordova, H.
(En, Es)
ilus., 7 ref.
Keywords: ZEA MAYS; HIBRIDACION; INTERACCION GENOTIPO AMBIENTE; COSTA RICA